Roadkills of wild mammals in an agro-landscape of Balsa de Atenas, Costa Rica - Carvajal-Sanchez, José Pablo (2023)
Roads are a significant threat to wildlife, in fact, many mammals are killed on Costa Rican roads each year, but the impact on the mammal communities is not yet understood. Objective. To determine the incidence of roadkill of wild mammals on Route 720 and its relationship to topographic variables of the road in Concepción de Balsa de Atenas, Alajuela, Costa Rica in the last 7 years (2015-2022). Methods: We analyzed road kills of mammals in route 720, Concepción de Balsa de Atenas, Alajuela, from 2015 to 2021.  The highest incidence of road killings occurred in a section of a straight segment and open curves of the road, where the road is close to living fences which are frequently used by wildlife as cover and corridors to travel.  Results: In total, 12 individuals were recorded killed by being run over, the species with the highest frequency of deaths on the roads was the common opossum (Didelphis marsupialis), which is consistent with other studies.  Conclusion. It is necessary to carry out studies in similar rural agro-landscapes that are crossed by roads, since these landscape mosaics of different land uses are important for the maintenance and persistence of wildlife.